190k views
2 votes
Complete the equation. Answer as a fraction in its simplest form. 9xy x (2/3x)^3=(__/__)x^4y

User Louanna
by
5.0k points

1 Answer

3 votes

Answer:

Fill the blank with
(8)/(3)

Explanation:

Given


9xy * ((2)/(3)x)^3 = (--/--)x^4y

Required

Fill in the gaps


9xy * ((2)/(3)x)^3 = (--/--)x^4y

Open Brackets


9xy * (2^3)/(3^3)x^3 = (--/--)x^4y


9xy * (8)/(27)x^3 = (--/--)x^4y

Multiply xy and x^3


9 * (8)/(27)x^4y = (--/--)x^4y


(9 * 8)/(27)x^4y = (--/--)x^4y

Divide fraction by 9/9


(8)/(3)x^4y = (--/--)x^4y

By comparison, the blank will be filled with:


(8)/(3)

Hence, the solution to the question is:
9xy * ((2)/(3)x)^3 = (8)/(3)x^4y

User Eggy
by
5.0k points